Cálculo e detalhamento prático de pilares para edificações de pequeno e médio porte - Miranda, Lucas Rodrigo (Universidade Federal de São Carlos, 2008)
Even the small buildinging column may have a buckled. It s denoted the difficulty to design and detail this type of element. So this work intends make a description and application of a several simplified process of presizing and column s design. The stability building procedures of the parameters a e γz are analyzed are applied to this kind of structure. Also it s detailing how the wind forces are important in the internal forces and how to consider it in the column s design. The reinforced and the wind force are calculate by using a free program obtains at the internet. Several examples are made considering a characteristic building with one, two, tree and four pavements showing how to analize the stability, the presizing and column s design and showing too the final results. All this samples are solved and compared with a professional program and the it show that all results are too close. Finally a lot of commentary how to design the columns are made to aided engineers to make a good column s design for small and medium buildinging.
Keywords: Colunas; Concreto armado; Instabilidade; Dimensionamento; Detalhamento construtivo; Column; Reinforced concrete; Instability; Design; Reinforcement; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL